Duchenne muscular dystrophy (DMD): Story and News - Takahashi-Ferrer, Carolina Mayo (2023)
In the mid-1800s, the first cases of patients with clinical details of a disease were presented, characterized by a gradual decrease in muscle that usually appears or is noticeable in the first 3 years of life. It was not until 52 years later that the British physician Edward Meryon (1809-1880) made the first precise descriptions, after studying muscle biopsies from four brothers, who all died before the age of 17, due to the fact that they had a disease called Duchenne muscular dystrophy, in memory of the valuable portraitist and physician Duchenne de Boulogne. The objective of this article is to detail the main authors who cooperated by providing a detailed description of patients with Duchenne muscular dystrophy, as well as to summarize the characteristics, etiology, treatment and problems in Peru.